2008
DOI: 10.1097/mpa.0b013e3181706d93
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Metallic Stents in Patients With Unresectable Pancreatic Cancer Receiving Gemcitabine

Abstract: Expandable metallic stent placement is safe and effective in patients with unresectable pancreatic cancer receiving GEM. Gemcitabine improves survival irrespective of EMS placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In direct contrast, systemic gemcitabine had no effects on stent patency or patient survival in the present study. Nakai et al 27. reported that gemcitabine-based systemic chemotherapy had no effects on stent-related complications or stent patency.…”
Section: Discussionmentioning
confidence: 99%
“…In direct contrast, systemic gemcitabine had no effects on stent patency or patient survival in the present study. Nakai et al 27. reported that gemcitabine-based systemic chemotherapy had no effects on stent-related complications or stent patency.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with unresectable pancreatic cancer, gemcitabine chemotherapy did not increase stent occlusion or stent‐related complications of SEMS. However, stent migration tended to be higher in the gemcitabine group (17% vs 3%) . In a further recent, large‐scale study of 291 biliary stents (151 SEMS and 140 PS), stent patency was comparable in cases with and without chemo (radio)therapy .…”
Section: Methodsmentioning
confidence: 99%
“…C-SEMSs and their antimigration properties have been evaluated in patients with benign pancreatobiliary strictures and malignant biliary obstruction. An improved prognosis in accordance with the recent development of chemotherapy will necessitate C-SEMS with longer patency without stent migration 3,4…”
Section: Introductionmentioning
confidence: 99%